2009
DOI: 10.1002/hep.23281
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A inhibits hepatitis C virus nonstructural protein 2 through cyclophilin A #

Abstract: Numerous anti-hepatitis C virus (HCV) drugs targeting either the viral nonstructural 3 (NS3) protease or NS5B polymerase are currently in clinical testing. However, rapid resistance development is a major problem and optimal therapy will clearly require a combination of multiple mechanisms of action. Cyclosporine A (CsA) and its nonimmunosuppressant derivatives are among the more promising drugs under development. Based on work with subgenomic HCV replicons it has been thought that they act as NS5B-inhibitors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
83
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 23 publications
2
83
0
Order By: Relevance
“…This suggests that SCD1 may be involved in an additional step as well as a replication step of the viral life cycle. Indeed, it has been reported previously that cyclophilin A inhibitors target multiple steps of the HCV life cycle and inhibit JFH1-derived full-length HCV more efficiently than subgenomic replicons (41,42). We also confirmed that SCD1 was not involved in HCV IRES-mediated translation.…”
Section: Discussionsupporting
confidence: 79%
“…This suggests that SCD1 may be involved in an additional step as well as a replication step of the viral life cycle. Indeed, it has been reported previously that cyclophilin A inhibitors target multiple steps of the HCV life cycle and inhibit JFH1-derived full-length HCV more efficiently than subgenomic replicons (41,42). We also confirmed that SCD1 was not involved in HCV IRES-mediated translation.…”
Section: Discussionsupporting
confidence: 79%
“…The power of this method is illustrated by NS5A and CypA. These two proteins are involved in HCV assembly (57,58); they cosediment with virions in density gradients (Figs. 1A and 2E), but they are not detectable in virus fractions after affinity purification (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also suggested that NS2, a cysteine protease, is an additional cyclophilin target (19,25). NS5A mutations, mostly located in the C-terminal half of the protein, were shown to confer the highest resistance against cyclophilin inhibitors (21,22).…”
mentioning
confidence: 99%